BLADE ANGLE EFFECT ON DROPLET SIZE SPECTRUM OF ROTARY ATOMIZERS USED IN BRAZIL - Carvalho,Fernando K. (2016)
ABSTRACT The effect of blade angle on droplet size spectrum of five rotary cage atomizers and one rotary disc atomizer used in Brazil was evaluated in a high speed wind tunnel, with an air speed of 180 km h−1. This study included the characterization of the droplet size spectrum, via laser diffraction instrument, generated by three blades angles, of 45, 60 and 75 degrees. The spray solution was composed of Picoxystrobin+ Cyproconazole fungicide (SC), at 20 mL c.p. L−1, and at a flow rate of 6 L min−1. As the angle decreased from 75 to 45 degrees, the rotational speed of the atomizers increased and the volume median diameter (VMD) decreased. However, increasing the rotational speed also increased the percentage of droplets smaller than 100 µm (% < 100 µm). At the blade angles of 45 and 60 degrees the atomizers showed that % < 100 µm was higher than 20% and VMD was smaller than 198 µm. The disc type atomizer resulted in the lower values of relative span (RS). The use of 75 degrees blade angle produced the highest values of VMD and the lowest values of % < 100 µm; these parameters were also affected by atomizer model and brand.